CURRENT APPROACHES TO TEACHING TUBERCULOSIS CONTROL WHEN INTRODUCING FEDERAL STATE EDUCATIONAL STANDARD OF HIGHER EDUCATION - O. V. Filinyuk; O. V. Kolokolova; L. N. Buynova; N. N. Kabanets; G. V. YAnova; N. A. Zemlyanaya (Туберкулез и болезни лёгких)
Goal: to investigate specific methods of tuberculosis control teaching to students of Pediatric and General Medicine Department at Phthisiology and Pulmonology Department of Siberian State Medical University subordinated to the Russian Ministry of Health.Materials and methods. Main training curricula and teaching programmes for professional lines of 31.05.01 on General Medicine and 31.05.02 on Pediatrics, students' questionnaires.Results. The article presents the experience of self-tuition of students while preparing to practical training in tuberculosis control in order to enhance the efficiency of mastering this topic, to form positive motivation to have training and productive activities, to develop the skills of information collection and its compilation for public presentation; it describes the task teachers face when implementing Federal State Educational Standard of Higher Education.Conclusions. It is necessary to optimize the training in order to enhance the self-tuition of students when preparing for practical training in tuberculosis control; new forms of training are to be introduced.